Value gap in Nigerian property compensation practice: measurement and economic effects. (3rd May 2016) - Bello, Nurudeen Akinsola; Olanrele, Olusegun Olaopin
Abstract: The compulsory acquisition of some properties by Ogun State Government, Nigeria, along urban roads for road expansion required compensation for the affected owners. Statutorily, Estate Surveyors and Valuers (ESVs) are the recognized professionals who determine property value in Nigeria. This paper seeks to measure the gap in values between those submitted by ESVs representing the government and those ESVs representing claimants for the same property to investigate the economic implication of the variation on the claimants and the ESVs representing claimants, through the administration of 409 questionnaires to the claimants and the claimants' ESVs. The findings indicate a gap in value of above 41% between claimant's ESV's and government's ESV's, leading to an 83.29% (NGN8.88 m) loss of fee to claimant's ESV's. It is suggested that the Nigerian Institution of Estate Surveyors and Valuers should recommend standardized building cost per square metre data and provide guidance on an acceptable value gap to minimize the observed wide value gap in the future.